Pengaruh Sistem Informasi Manajemen Terhadap Efektivitas Kerja Pegawai Pada Kantor Kecamatan Banjarsari Kabupaten Ciamis - Ajat Sudrajat; Nana Darna; Nurdiana Mulyantini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The problems faced in this study include (1) How is the management information system in the Banjarsari District Office, Ciamis Regency. (2) How is the effectiveness of employee work at the Banjarsari District Office, Ciamis Regency. (3) How does the management information system affect the effectiveness of employee work at the Banjarsari District Office, Ciamis Regency This study aims to study, find out, and analyze (1) The management information system in the Banjarsari District Office, Ciamis Regency. (2) The effectiveness of employee work at the Banjarsari District Office, Ciamis Regency. (3) The effect of the management information system on the effectiveness of employee work at the Banjarsari District Office, Ciamis Regency The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Simple Linear Regression. The results of the study inform that (1) The information management system in the Banjarsari District Office, Ciamis Regency is very high. The highest value on the system quality indicator and the lowest value on the usage indicator. (2) The effectiveness of employee work at the Banjarsari District Office, Ciamis Regency is very high. The highest value on the time measurement indicator and the lowest value on the result measurement indicator. (3) The information management system has a positive effect on the effectiveness of employee work at the Banjarsari District Office, Ciamis Regency. This means that if the information management system is improved, the effectiveness of employee work at the Banjarsari District Office, Ciamis Regency will also increase.